EVALUATION OF SUBMERGED HEALING OF COLONIC ANASTOMOSES IN SURGICAL HOSPITAL - V. V. Leonov; Y. L. Shalkov; A. V. Leonov; Abbas Hamed (Кубанский научный медицинский вестник, 2014)
Thus, the main causes of «hand technique» anastomosis by invagination are technical defects of the intervention in telescopic anastomosis by invagination and the ischemic disorders in colorectal anastomosis by invagination. 48 patients were operated on the colon and rectum with «hand technique» anastomosis. Invalidated «manual technique» anastomosis after 70 days of the formation were fully functional, and processes of healing and morphological transformation of mucosa were completed.